Parametric Optimization of Biomass Steam-and-Gas Plant - V. Sednin; A. Levshenia (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper contains a parametric analysis of the simplest scheme of a steam-and gas plant for the conditions required for biomass burning. It has been shown that application of gas-turbine and steam-and-gas plants can significantly exceed an efficiency of steam-power supply units which are used at the present moment. Optimum thermo-dynamical conditions for application of steam-and gas plants with the purpose to burn biomass require new technological solutions in the field of heat-exchange equipment designs.